Confirmatory Factor Analysis (CFA) of Tourismpreneurship Based on Village Index Dimensions in Enhancing Tourism Competitiveness - Haryono, Gampo; Rio Baviga; Efrianto; Ingga Kharisma Degama; Anton Setiawan (Citakonsultindo, 2026)
Village-based tourism plays an important role in promoting inclusive and sustainable local economic development, particularly in rural areas with strong natural and cultural potential. However, tourism development in many villages is constrained by uneven entrepreneurial capacity and limited supporting economic infrastructure. This study aims to develop and validate a tourismpreneurship measurement model based on Village Index dimensions, focusing on the economic dimension, using Confirmatory Factor Analysis (CFA). The research was conducted in Kerinci Regency, Indonesia, involving 285 villages through a full sampling approach. Data were collected using structured questionnaires with a five-point Likert scale and analyzed using IBM SPSS AMOS. The economic dimension was operationalized through two latent constructs: Village Production (four indicators) and Economic Support Facilities (eight indicators). The CFA results indicate an acceptable model fit (CMIN/DF = 2.439; GFI = 0.928; RMSEA = 0.071). Village Flagship Products (λ = 0.866) and Postal and Logistics Services (λ = 0.616) emerge as the most influential indicators. The moderate correlation between constructs (r = 0.403) confirms discriminant validity. These findings support the use of the Village Index framework to strengthen tourismpreneurship and village tourism competitiveness. This study contributes theoretically by integrating tourismpreneurship within the Village Index framework and methodologically by validating a multidimensional economic model using CFA.